Comparison of caries and oral hygiene status of child laborers and school children: A cross-sectional study - Chanchal Gangwar; Manish Kumar; L Nagesh (Wolters Kluwer Medknow Publications, 2015)
Background: Child labor is recognized as a global health problem and child laborers are exposed to unique living, working conditions and face such events in life, which are not usually faced by other children. Research on its health impact and oral health impact has been very limited and inconsistent. Aim: The aim was to assess and compare dental caries and oral hygiene status of child laborers and school children of Bareilly city. Materials and Methods: A total of 400 child laborers by snowball sampling technique and 400 school children by random sampling technique were included in the study. A specially designed pretested proforma was used to collect data related to the sociodemographic profile, adverse habits and frequency of dental visits. Decayed, missing, and filled teeth index (DMFT) and oral hygiene index-simplified (OHI-S) were used. Results: The mean age of child laborers and school children was 13.07 ± 1.3 and 13.03 ± 1.5. The majority of child laborers (82.8%) had no mouth rinsing habit. Tobacco-related habits were found among 37.8% of child laborers. Most of the child laborers (91%) never visited dentists. The mean DMFT was 3.8 ± 1.7 and 2.9 ± 1.6 for child laborers and school children, respectively, (P < 0.05). The mean OHI-S score was 2.3 ± 0.70 and 2.1 ± 0.9 in child laborers and school children, respectively, (P < 0.05). Conclusion: The study demonstrated that the child laborers have poorer oral health status with respect to dental caries and oral hygiene compared to school children.